Continuity of care and advanced prostate cancer - Ravishankar Jayadevappa; Thomas Guzzo; Neha Vapiwala; Stanley Bruce Malkowicz; Joseph J. Gallo; Sumedha Chhatre (Cancer Medicine, 2023)
Abstract Background Continuity of care is an important element of advanced prostate cancer care due to the availability of multiple treatment options, and associated toxicity. However, the association between continuity of care and outcomes across different racial groups remains unclear. Objective To assess the association of provider continuity of care with outcomes among Medicare fee‐for‐service beneficiaries with advanced prostate cancer and its variation by race. Design Retrospective cohort study using Surveillance, Epidemiology, and End Results (SEER)‐Medicare data. Subjects African American and white Medicare beneficiaries aged 66 or older, and diagnosed with advanced prostate cancer between 2000 and 2011. At least 5 years of follow‐up data for the cohort was used. Measures Short‐term outcomes were emergency room (ER) visits, hospitalizations, and cost during acute survivorship phase (2‐year post‐diagnosis), and mortality (all‐cause and prostate cancer‐specific) during the follow‐up period. We calculated continuity of care using Continuity of Care Index (COCI) and Usual Provider Care Index (UPCI), for all visits, oncology visits, and primary care visits in acute survivorship phase. We used Poisson models for ER visits and hospitalizations, and log‐link GLM for cost. Cox model and Fine‐Gray competing risk models were used for survival analysis, weighted by propensity score. We performed similar analysis for continuity of care in the 2‐year period following acute survivorship phase. Results One unit increase in COCI was associated with reduction in short‐term ER visits (incidence rate ratio [IRR] = 0.65, 95% confidence interval [CI] 0.64, 0.67), hospitalizations (IRR = 0.65, 95% CI 0.64, 0.67), and cost (0.64, 95% CI 0.61, 0.66) and lower hazard of long‐term mortality. Magnitude of these associations differed between African American and white patients. We observed comparable results for continuity of care in the follow‐up period. Conclusions Continuity of care was associated with improved outcomes. The benefits of higher continuity of care were greater for African Americans, compared to white patients. Advanced prostate cancer survivorship care must integrate appropriate strategies to promote continuity of care.